Spatio‐Temporal Analysis of Pan Evaporation in Iran Using Quantile Trend Regression and Mann‐Kendall Methods - Ahmad Reza Ghasemi; Marziyeh Esmaeilpour (Earth and Space Science)
Abstract Trends in pan evaporation are regarded as indicators for studying climate change. This study analyzed the spatial and temporal changes in pan evaporation (PE) from 130 stations with at least 40 years of data in Iran. For this purpose, the quantile trend method at the 10th, 50th and 90th quantiles, along with the Mann‐Kendall and Sen's slope methods, were employed. The findings revealed that, on average, significant negative and positive trends changed by 16.4 and 17.8 mm/decade, respectively. The most significant negative trends were observed near water bodies in the north and south of Iran. Meanwhile, air temperatures increased significantly from 0.20 to 0.28°C/decade in the north and from 0.13 to 0.24°C/decade in the south. This rise in temperature led to a corresponding increase in specific humidity, which could reduce pan evaporation. The quantile trend analysis showed that, at stations with significant negative trends, the monthly high evaporation values generally decreased (−3.3 to −11 mm/decade) more than the monthly low evaporation values (−2.2 to −6.5 mm/decade). Conversely, at significant positive trends, the slopes in low evaporation values (2.0–6.7 mm/decade) exceeded those in high evaporation (1.8–4.0 mm/decade). On the seasonal time scale the reduction in pan evaporation during summer was more than in spring. Forthermore, the results suggested that the evaporation paradox in the western and northwestern regions was more pronounced than in other areas.